The Role of Transabdominal Ultrasound Elastography in Gastrointestinal Non-Liver Diseases: Current Application and Future Prospectives - Mattia Paratore; Matteo Garcovich; Maria Elena Ainora; Livio Enrico Del Vecchio; Giuseppe Cuccia; Laura Riccardi; Maurizio Pompili; Antonio Gasbarrini; Maria Assunta Zocco (Diagnostics, 2023)
Ultrasound imaging is the first-line investigation for patients with abdominal symptoms, as it effectively depicts the gastrointestinal tract and enables the diagnosis of multiple pathological conditions. Among different recent ultrasound technological advancements, elastography enables the evaluation of various tissue characteristics, such as neoplastic transformation or fibroinflammatory status. In recent years, ultrasound elastography has been utilized extensively for the study of liver diseases and in numerous other clinical settings, including gastrointestinal diseases. Current guidelines suggest the use of transabdominal ultrasound elastography to characterize bowel wall lesions, to assess gastrointestinal contractility, to diagnose and grade chronic pancreatitis; however, no specific indications are provided. In the present paper, we summarize the evidence concerning the application of different ultrasound elastography modalities in gastrointestinal non-liver diseases.